Mathematical model for motion of weighted parts in curled flow - Batluk, V.; Basov, M.; Klymets, V. (Національний університет "Львівська політехніка", 2013)
The article deals with the problem of providing high performance apparatuses for cleaning air from dust in various branches of industry in order to reduce hazardous emissions to the level conforming to sanitaryhygienic norms. The article describes new trends in the development of dust catching apparatuses based on the use of centrifugal-inertial forces, permitting to improve significantly the effectiveness of dust catching.
Keywords: dust catching; air cleaning; pollution; centrifugal; cyclone